2017
DOI: 10.1186/s12967-017-1345-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and autoantibody clusters interaction in systemic lupus erythematosus

Abstract: BackgroundEvidence supports the existence of different subphenotypes in systemic lupus erythematosus (SLE) and the pivotal role of cytokines and autoantibodies, which interact in a highly complex network. Thus, understanding how these complex nonlinear processes are connected and observed in real-life settings is a major challenge. Cluster approaches may assist in the identification of these subphenotypes, which represent such a phenomenon, and may contribute to the development of personalized medicine. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 78 publications
1
35
1
2
Order By: Relevance
“…It is widely appreciated that SLE can manifest in various forms and that autoantibody profiles can subdivide patients into more homogeneous groups 13–15. Also, it is possible that stratification of patients powered by machine learning techniques will lead to a novel, molecular-based nomenclature of disease that will likely improve patient outcome 16.…”
Section: Lupus As a Heterogeneous Group Of Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely appreciated that SLE can manifest in various forms and that autoantibody profiles can subdivide patients into more homogeneous groups 13–15. Also, it is possible that stratification of patients powered by machine learning techniques will lead to a novel, molecular-based nomenclature of disease that will likely improve patient outcome 16.…”
Section: Lupus As a Heterogeneous Group Of Symptomsmentioning
confidence: 99%
“…For clinical trials in patients with AARD, ANA, even if clearly defined, is unlikely to provide the full insight into meaningful disease subsets of patients who respond to a particular treatment. Along those lines, autoantibodies might not provide a robust reflection of pathogenic pathways where other biomarkers such as cytokines, inflammatory proteins or complement components can provide further insights into potential treatment strategies 15…”
Section: Lupus As a Heterogeneous Group Of Symptomsmentioning
confidence: 99%
“…Additionally, excessive pro-inflammatory cytokine release may also promote SLE development (3)(4)(5)(6).…”
Section: ' Introductionmentioning
confidence: 99%
“…In contrast, group 2 contained increased levels of CXCL10 and CXCL13. In a study of 67 patients by Pacheco et al (2017), using cytokine levels alone four groups were identified: neutral, chemokine, G-colony stimulating factor (G-CSF)-dominant and IFNα/pro-inflammatory [ 21 ]. Despite marked differences in the cytokines measures, our larger study also demonstrates “chemokine” and “cytokine” clusters of patients.…”
Section: Discussionmentioning
confidence: 99%